PROMOTION OF HEALTHY LIFESTYLE IN HISTORICAL AND SOCIAL RETROSPECTIVE REVIEW: FROM THE RENAISSANCE EPOCH TO THE PRESENT TIME - В. Бобрицька (Київський національний університет імені Тараса Шевченка, 2017)
The article reveals the key ideas, historical course of the scientific opinion on promotion of the healthcare culture at different times – from the Renaissance to the present time (during the ХІV–ХХІ centuries). There have been applied theoretical methods, namely: historical and structural; chronological; diachronic ones.In a description of the retrospective of arising and solving problems of promoting healthy lifestyle of a person found that the most significant milestones can be considered the ones as follows: specifying by the thinkers of the sixteenth century the sphere of natural human desires and feelings, while humanists and artists of the Renaissance can be distinguished for glorification of human vital energy. It has been proved to be essential that the addressing to promotion-related issues of healthy lifestyle of modern person concerns revision existing behaviour stereotypes, rethinking of the conceptual model of healthy lifestyle with regard to the fact that lifestyle performs the leading role in maintaining and strengthening health.It has been proved that in the modern education system there is strategically increasing demand for developing and implementing educational technologies, which would strengthen the young person's responsibility for their health and promote the idea that their welfare correlates to the state of health as much as to the level qualification. In the author's view, the cultural aspect of the problem is crusial in health saving as health culture reflects the extent of a perception by the person their attitude to oneself, society and nature.Having considered best practices in promoting healthy lifestyle seen in the retrospective view of historical and social aspects there have been worked out the recommendations that can be used to develop modern strategy to be applied to the sphere of Ukrainian citizens' health saving, and the further outlined points should be taken into account: first, the results of the monitoring-aimed study of the health condition of all age groups of the population and its dynamics; second, the there were specified mechanisms of implementation of the seriesof regulations, programmes aimed at maintaining health of young people in an educational environment; third, there was specified the role of each socio-economic structure (family, educational institutions, public healthcare system, industrial facilities, sports and recreation organizations, government agencies, civil society institutions, etc.) in solving the problems of protecting, saving and strengthening the health of children and youth in Ukraine.

Висвітлено історичний перебіг розвитку наукової думки щодо культивування здоров'я в різні часи – від епохи Відродження дотепер (період ХІV–ХХІ ст.); обґрунтовано, що звернення до проблеми культивування здоров'я сучасної людини, потребує перегляду сформованих стереотипів її поведінки з урахуванням значущості способу життя; на основі аналізу досвіду культивування здоров'я в історико-соціальній ретроспективі розроблено рекомендації, що можуть бути використані для створення сучасної стратегії України у сфері здоров'язбереження населення.
КУЛЬТИВУВАННЯ ЗДОРОВ'Я В ІСТОРИКО-СОЦІАЛЬНІЙ РЕТРОСПЕКТИВІ: ВІД ЕПОХИ ВІДРОДЖЕННЯ ДО СЬОГОДЕННЯ
Keywords: культивування здоров'я; здоров'язбереження; здоровий спосіб життя; ЗСЖ; promotion of healthy lifestyle; health saving; healthy lifestyle